Acceleration of fungal spore production by embedding a hydrophobic polymer net in a nutrient agar plate. Issue 2 (February 2019) - Oda, Shinobu; Kido, Ryosuke
Abstract: A simple and novel procedure for the acceleration of fungal spore production was developed. A net of hydrophobic polymer such as polypropylene (PP) and polytetrafluoroethylene (PTFE) was embedded in a nutrient agar plate, and effect of the polymer net on spore production by 6 fungal strains, such as Aspergillus terreus, Penicillium multicolor, and Trichoderma virens were estimated. The effect of hydrophobic polymer net was insufficient in a liquid-surface immobilization (LSI) system with fungal cells immobilized on a ballooned microsphere layer formed on a liquid medium surface. On the other hand, the embedding of a PTFE net in an agar plate remarkably enhanced the spore production in all 6 strains tested to produce 2.0–8.5 × 10 7 spores/cm 2 -agar plate surface. Especially, the spore production by A . terreus ATCC 20542 in the presence of a PTFE net was 7.7 times as much than that in no net. Positive correlations between the hydrophobicity of net and the spore production were observed in all 6 strains ( R 2, 0.653–0.999). Graphical abstract: Image 1 Highlights: A simple and novel procedure of fungal spore production was developed. Liquid-surface immobilization system was unsuitable for spore production. Embedding a hydrophobic polymer net in an agar plate enhanced spore production. Effective hydrophobic polymers are polypropylene and polytetrafluoroethylene.